105k views
2 votes
True or false: In(x+y)- In(x+y)=0. Explain your thinking.

User Foslock
by
5.0k points

2 Answers

5 votes

Answer:

In(x+y) - In(x+y)

= In(
(x + y)/(x + y))

= In(1)

=0

Hence, the statement is true!!

User Manduro
by
4.7k points
1 vote


\huge \bf༆ Answer ༄

Let's solve ~


  • \sf ln(x + y) - ln(x + y)


  • \sf ln( (x + y)/(x + y) )


  • \sf ln(1)


  • \sf0

[ Since, ln (1) = 0 ]

Therefore, the statement is true ~

User Soyoung
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.